Accounting of infiltration waters and the level of recharge of the root layer by groundwater when calculating the irrigation regime on drained lands - Mazhaysky Yuri; Pavlov Artyom (BIO Web of Conferences)
The paper provides a justification for the need to take into account the inflow of infiltration waters into the soil profile and groundwater recharge when calculating the irrigation regime of agricultural crops. The studies were performed on sod-podzolic sandy loam soils with a close groundwater level in the territory of the Meshcherskaya lowland in the southern part of the Non-Chernozem zone of Russia. Based on the research results, the methodology for determining the parameters of the water balance and calculating the water regime of light mineral soils has been improved. It is proposed to adjust the irrigation system according to the developed methodology, taking into account daily water consumption and vertical moisture exchange. The developed algorithm for calculating irrigation standards, which takes into account the movement of infiltration and groundwater, will reduce the irrigation rate by 1.3 times on drained soils. The implementation of the methodology will make it possible to optimize land reclamation measures and increase the efficiency of agricultural production.